(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Self-confidence is a critical factor in students’ success in language learning, particularly in speaking classes where anxiety and fear of making mistakes often hinder participation. This article explores various strategies that educators can employ to enhance students’ self-confidence in speaking activities. It highlights the importance of creating a supportive and positive classroom environment, using lowstakes activities to reduce pressure, and encouraging preparation and practice to build fluency. Additionally, the article discusses the role of technology, fun activities, and individualized goals in fostering a more confident speaking experience. By implementing these methods, teachers can help students overcome their fears, build their speaking abilities, and engage more fully in language learning.